Creating value through people : discussions with talent leaders - Mercer (Firm) (Hoboken, N.J. : Wiley, 2009)
"Creating Value Through People: Discussions with Talent Leaders contains unique stories through interviews with human capital innovators from diverse backgrounds, many told for the first time." "These innovators have been selected for their singular views and perspectives on inspiring, encouraging, and leading people to do their best, both in and outside of the workplace." "Each of the twenty interviews in this user-friendly book captures the spirit and the substance of people whose insight and actions have helped raise the bar in defining what people can accomplish. Indeed, you'll find diverse, compelling views on a variety of topics."
"Providing a wealth of hands-on, practical experience, this book provides your organization with the tools, facts, and know-how to empower people to deliver their best performance. Representing the research Mercer is undertaking with regard to talent innovators and talent innovation, Creating Value Through People will motivate you to perform at your best and to focus your efforts in ways that create measurable value."--Jacket
Chapter 1 Mike Abrashoff: Former Comander, USS Benfold (Retired U.S. Navy) 5 -- Chapter 2 Jan Fields: Executive Vice President and Chief Operating Officer, McDonald's Corporation 23 -- Chapter 3 Dr. Victor Fung: Group Chairman of the Li & Fung Group of Companies 35 -- Chapter 4 Anne Ruddy: Executive Director, WorldatWork 45 -- Chapter 5 Dr. Richard Boyatzis: Professor, Weatherhead School of Management, Case Western Reserve University 59 -- Chapter 6 Robert Joy: Former Senior Vice President, Human Resources, Colgate-Palmolive Professor, Executive Masters in Human Resource Leadership Program, Rutgers University 71 -- Chapter 7 Joel I. Klein: Chancellor of the New York City Department of Education 83 -- Chapter 8 John Tyson: Chairman, Tyson Foods 107 -- Chapter 9 Tom Kelley: Chief Executive Officer, IDEO 121 -- Chapter 10 Simon F. Cooper: President, Chief Operating Officer, The Ritz-Carlton Hotel Company, LLC 139 -- Chapter 11 Henri A. Termeer: Chairman, President, and CEO of Genzyme Corp 157 -- Chapter 12 Gordon Bethune: Former Chairman and CEO, Continental Airlines 179 -- Chapter 13 Linda A. Hill: Wallace Brett Donham Professor of Business Administration, Harvard Business School 191 -- Chapter 14 Billy Beane: Vice President and General Manager, Oakland Athletics Baseball Team 199 -- Chapter 15 Micky Arison: Chairman, CEO, Carnival Corporation 207 -- Chapter 16 Linda Smith: Founder, President and Chief Executive Officer, Four-D College 213 -- Chapter 17 Ilene H. Lang: President and CEO, Catalyst 223 -- Chapter 18 Ron Sargent: CEO of Staples, Inc. 235 -- Chapter 19 Jerry (Yoram) Wind: The Lauder Professor, The Wharton School Founder, Wharton School Publishing 253 -- Chapter 20 Howard Behar: Former President, Starbucks North America Former President, Starbucks International Member, Starbucks Board of Directors 265.
Print version record.
John Wiley and Sons
Keywords: Leadership; Personnel management; Employee motivation; Leadership; Personnel -- Direction; Personnel -- Motivation; BUSINESS & ECONOMICS -- Leadership; Employee motivation; Leadership; Personnel management